Hypertension in NF1: A closer look at the primacy of essential hypertension versus secondary causes - Loponen, Niina (John Wiley & Sons, 2025)
Background
We aimed to analyze hypertension in neurofibromatosis type 1 (NF1) in a Finnish population-based cohort in 1996–2014.
Methods
A cohort of 1365 individuals with confirmed NF1 was compared with a control cohort of 13,923 individuals matched for age, sex, and area of residence. Diagnoses of hypertension were retrieved from the Finnish Care Register for Health Care. These registered data were separately analyzed for secondary and essential hypertension. Purchases of antihypertensive drugs were queried from the Finnish Register of Reimbursed Drug Purchases.
Results
We identified 115 NF1 patients with hospital diagnosis of hypertension. Our findings revealed a hazard ratio (HR) of 1.64 (95% CI 1.34–2.00, p < 0.001) in NF1 versus controls. NF1 patients presented with a significantly increased hazard for both secondary hypertension (n = 9, HR 3.76, 95% CI 1.77–7.95, p < 0.001) and essential hypertension (n = 98, HR 1.73, 95% CI 1.39–2.14, p < 0.001). No difference in the HR of hypertension was observed between men and women, while NF1 patients with essential hypertension were, on average, younger than the controls. The proportions of individuals with antihypertensive medication did not differ between NF1 patients and controls (OR 0.85).
Conclusion
NF1 is a risk factor for hypertension. Despite the recognized risk for secondary hypertension, essential hypertension is the predominant type in NF1.